Implementation of Student’s Discipline Character and the Role of Educators at SDN 241 Palembang - Novrianti, Fenni; Widayatsih, Tri; Mahasir, Mahasir (Yayasan Sembilan Pemuda Indonesia, 2024)
Implementing discipline character among students and the role of educators in elementary schools are crucial aspects in shaping a well-rounded individual. This study investigates the strategies used to instill discipline in students and the involvement of educators in this process at. The study employs a qualitative approach, utilizing interviews, observations, and documentation analysis to gather data. Results indicate that a combination of consistent routines, clear rules, and positive reinforcement effectively promotes student discipline. Educators play a significant role, not only as enforcers of laws but also as role models and mentors, guiding students toward self-discipline. The findings suggest that an integrated approach involving the school community and parents enhances the effectiveness of discipline character building. This study contributes to the understanding of character education in elementary schools and offers practical recommendations for educators and policymakers to foster a disciplined and conducive learning environment.